Microwave disinfection of maxillary and mandibular denture bases contaminated with Candida Albican (2015)
Background: Oral environment is not sterile, and dentures worn by the patients can be infected and therefore needs disinfection. Solution disinfectants such as sodium hypochlorite and glutaraldehyde can be used but they have side effects. Microwave disinfection method is more recent, however, there are conflicting reports at the moment on the appropriate power and time regimen for disinfection of denture. Objective: To determine the power and time regimen at which the disinfection of dentures can be achieved using microwave. Method: Forty-five acrylic denture bases were fabricated for each of the jaws and infected with solution of a stock Candida albicans and 30 infected bases were employed as control. These were placed in normal saline and then subjected to different microwave power and time regimen. Aliquots from these post-microwave solution were titrated against sabauraud agar which was subsequently incubated at 37oC for 48 hours. The agar were examined for candida growth. Result: The denture bases subjected to microwave disinfection at 350W showed Candida growth after microwave treatment irrespective of the time employed. Conversely, those microwaved at 650W and 690W for four and six minutes showed no microbial growth. Conclusion: The microwave regimen of 650W at 4 and 6 minutes completely disinfected the denture bases. Disinfection at higher microwave energy should be done with caution as distortion of the denture may occur.